2015
DOI: 10.1002/sec.1394
|View full text |Cite
|
Sign up to set email alerts
|

A secure white-box SM4 implementation

Abstract: White‐box cryptography aims at implementing a cipher to protect its key from being extracted in a white‐box attack context, where an attacker has full control over dynamic execution of the cryptographic software. So far, most white‐box implementations exploit lookup‐table‐based techniques and have been broken because of a weakness that the embedded large linear encodings are cancelled out by compositions of lookup tables. In this paper, we propose a new lookup‐table‐based white‐box implementation for the Chine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In 2014, Luo et al [10] improved on Xiao et al's white-box AES using nonlinear encoding. In 2016, Bai et al [11] proposed a white-box implementation of the SM4 algorithm (denoted as Bai-Wu SM4 white-box scheme) using the same construction of lookup tables. To improve efficiency, the Bai-Wu SM4 white-box scheme uses two types of lookup tables: one to perform output decoding and encoding of new inputs, and the other to compute the wheel function of the standard SM4 algorithm.…”
Section: Realated Workmentioning
confidence: 99%
“…In 2014, Luo et al [10] improved on Xiao et al's white-box AES using nonlinear encoding. In 2016, Bai et al [11] proposed a white-box implementation of the SM4 algorithm (denoted as Bai-Wu SM4 white-box scheme) using the same construction of lookup tables. To improve efficiency, the Bai-Wu SM4 white-box scheme uses two types of lookup tables: one to perform output decoding and encoding of new inputs, and the other to compute the wheel function of the standard SM4 algorithm.…”
Section: Realated Workmentioning
confidence: 99%
“…Bai and Wu 27 proposed a protected white‐box SM4 execution to secure large linear encodings from canceling. Speed, memory, attacks such as BGE, MGH was the performance measures that are evaluated in this approach.…”
Section: Recent Related Work: a Reviewmentioning
confidence: 99%
“…They demonstrated that the worst-case time complexity to obtain the key of the Xiao-Lai scheme was O 2 47 . In 2016, Bai et al [12] employed more complicated encodings and larger tables to prevent the cancellation of higher-order linear encodings through combinatorial lookup tables, and proposed the Bai-Wu scheme. The scheme runs nine times faster than the Xiao-Lai scheme but requires 32.5 MB of memory for storing lookup tables.…”
Section: Introductionmentioning
confidence: 99%